Transformations of 6PPD and 6PPD-quinone in soil under redox-driven conditions: Kinetics, product identification, and environmental implications - Dahang Shen; Qingyang Shi; Jingjing Zhang; Nathan D. Sy; Rebecca Yates; Wei Wang; Jay Gan (Environment International)
The pervassive release of tire and road wear particles (TRWPs) introduces the tire additive 6PPD and its biologically active derivative, 6PPD-quinone (6PPD-Q), into the environment, with soil serving as the primary sink. However, at present their fate in soil is largely unknown. This study considered the transformation kinetics and products (TPs) of 6PPD and 6PPD-Q under different soil conditions. In anaerobic soils, 6PPD persisted substantially longer (average half-life 51.4 d) than in aerobic soils (0.7–1.5 d), indicating that submerged soil or sediment compartments may serve as a more important secondary source. The degradation of 6PPD-Q in soils was mediated by microorganisms, with half-lives (13.5–14.2 d) longer than those of 6PPD under aerobic conditions. Distinct transformation pathways were observed for 6PPD and 6PPD-Q in soil under aerobic and anaerobic conditions, with 10 and 7 TPs identified, respectively. Two of the identified TPs, 1,3-dimethylbutylamine and N-phenyl-p-benzoquinone imine, are known to pose potential human exposure risks. The primary transformation reactions for 6PPD involved C-N cleavage, dehydrogenation, hydroxylation, and amination, while those for 6PPD-Q included dephenylation, hydroxylation, methylation, and amination. The study findings provide critical data for a better understanding of the environmental fate and risks of 6PPD and 6PPD-Q in terrestrial environments and offer valuable insights for pollution control strategies and policy development regarding these and other tire additives.